2019
DOI: 10.1111/pbi.13105
|View full text |Cite
|
Sign up to set email alerts
|

A wheat NAC interacts with an orphan protein and enhances resistance to Fusarium head blight disease

Abstract: Summary Taxonomically‐restricted orphan genes play an important role in environmental adaptation, as recently demonstrated by the fact that the Pooideae‐specific orphan TaFROG (Triticum aestivum Fusarium Resistance Orphan Gene) enhanced wheat resistance to the economically devastating Fusarium head blight (FHB) disease. Like most orphan genes, little is known about the cellular function of the encoded protein TaFROG, other than it interacts with the central stress regulator TaSnRK1α. Here, we functionally char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 84 publications
2
54
0
Order By: Relevance
“…It is likely that TaFROG functions in defense against F. graminearum by protecting TaSnRK1α against Osp24-mediated degradation. A recent report showed that TaFROG also interacts with TaNACL-D1, a Poaceae-divergent NAC transcription factor with its NAC C-terminal region specific to the Triticeae, to enhance FHB resistance independent of its interaction with TaSnRK1α 29 . It is possible that Osp24 also interacts with TaNACL-D1 to suppress defense against FHB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that TaFROG functions in defense against F. graminearum by protecting TaSnRK1α against Osp24-mediated degradation. A recent report showed that TaFROG also interacts with TaNACL-D1, a Poaceae-divergent NAC transcription factor with its NAC C-terminal region specific to the Triticeae, to enhance FHB resistance independent of its interaction with TaSnRK1α 29 . It is possible that Osp24 also interacts with TaNACL-D1 to suppress defense against FHB.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TaFROG that encodes a Pooideae-specific orphan protein induced by DON treatment also increased resistance against F. graminearum 28 . In wheat, TaFROG interacts with the TaSnRK1α protein kinase 28 and a NAC transcription factor 29 . Although germplasm with complete resistance or immunity to F. graminearum is lacking, more than 50 quantitative trait loci (QTLs) conferring various degrees of FHB resistance have been identified in wheat.…”
mentioning
confidence: 99%
“…The Pooideae-restricted gene TaFROG (Triticum aestivum Fusarium Resistance Orphan Gene) was shown to enhance wheat resistance to the Fusarium mycotoxin and virulence factor deoxynivalenol (DON) and it also enhanced resistance to Fusarium head blight (FHB) caused by Fusarium graminearum. TaFROG interacts with proteins of diverse cellular function, including the evolutionarily conserved SnRK1 (Sucrose-non-Fermenting Kinase) subfamily, illustrating TRG integration into conserved signaling processes (Perochon et al, 2015(Perochon et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the poplar NAC13 gene plays a vital role in the salt stress response [20]. Over-expression of a wheat NAC (TaNACL-D1) enhances resistance to Fusarium head blight disease [21], TaNAC30 negatively regulates the resistance of wheat to stripe rust [22], and TaNAC29 can provide salt stress tolerance by enhancing the antioxidant systems [23]. Over-expression of TsNAC1 from the halophyte Thellungiella halophila was shown to improve abiotic stress resistance, especially salt stress tolerance [24].…”
Section: Introductionmentioning
confidence: 99%